2,4-Thiazolidinedione in Treating Diabetes: A Comprehensive Overview - History, Chemistry, Advancements, Challenges and Future Perspectives (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Thiazolidinones are insulin-sensitizing agents used in the management and treatment of diabetes mellitus. Saturated at 5 positions, the thiazolidinedione compound is more active than the corresponding unsaturated compound. In some cases, 2,4-oxazolidinedione derivatives have shown superior anti-diabetic activity compared to 2,4-thiazolidinediones. Hydrophobic interactions between the N-alkyl group and the tail group of the aromatic ring of the TZD ligand and the receptor have been identified as crucial for the potent anti-hyperglycemic activity observed. This group of chemicals, called TZDs, includes indole, benzofuran, imidazopyridine, purines, pyridines, benzimidazole, phthalazinone, and benzoxazinone. The modification of the ether linker with ketone, alcohol olefin, amine, and acyl linker demonstrate modern to high anti-diabetic activity. Dual PPARα/γ agonists have the advantage of treating hyperglycemia and hyperlipidemia associated with T2DM. Unlike TZDs, which only bind and activate the PPARα/γ protein, phenyl propionic acid compounds have dual PPARα/γ agonist activity. Non-thiazolidinedione (non-TZD) compounds that activate PPARs are essential for managing hyperglycemia in diabetic patients. Drug development has targeted PPARs to treat diabetes mellitus and obesity, anti-inflammatory and cardiovascular disease. However, while glitazones have shown efficacy, they have also been linked with adverse drug reactions such weight gain, hepatotoxicity, osteoporosis and increased myocardial risk.